FRI0529 Initial Validation of The Symptoms in Persons at Risk of Rheumatoid Arthritis (SPARRA) Questionnaire. (15th July 2016) - Beers-Tas, M.V.; Tuyl, L.V.; Maat, B.; Hoogland, W.; Stack, R.; Raza, K.; Schaardenburg, D.V.
Abstract : Background: A range of clinical symptoms can be present in people at risk of rheumatoid arthritis (RA). However, information on location, timing, severity and predictive value of symptoms is still largely lacking. The Symptoms in Persons At Risk of Rheumatoid Arthritis (SPARRA) questionnaire has been developed with support of EULAR to provide more insight into these symptoms 1, 2 . Objectives: To validate the SPARRA questionnaire in an international group of arthralgia patients at risk of RA. Methods: Questions on presence, severity, impact and location of 13 symptoms were derived from a qualitative study in seropositive arthralgia patients 1 . The items are: joint pain or swelling, joint stiffness, burning and tingling sensations, numbness, change in skin colour, muscle cramps, weakness, fatigue, emotional distress, concentration difficulties and sleep problems. Answers are given on an ordinal scale. The number of days with a symptom per month (0, 1–5, 6–15, 16–30 days), severity (none, mild, moderate and severe) and influence on daily activities (no, small, moderate or high impact) were recorded. Finally, patients were asked to describe the pattern of symptom development over time. For this initial analysis of validity, patients were selected from the Dutch arthralgia cohort. We first administered the questionnaire to 30 patients to ask for ambiguities. Thereafter, 46 patients did a test-retest within one week to assess intra-rater agreement using the % agreement and the kappa score. Results: Feedback on the questionnaire was received from 5/30 patients. There were only minor comments that did not lead to adaptations, such as difficulty distinguishing pain from stiffness (n=1) and difficulty describing muscle cramps (n=1). 46 arthralgia patients were assessed at 2 time points. The rater agreement was moderate to good for most items with kappa's of 0.42 to 0.93. We also found acceptable percentages of agreement of 65 to 91 (Table 1 ). Only tingling sensations and numbness scored low in agreement, with kappa's of 0.37 and 0.15, respectively. The kappa's were good across the presence, severity and impact of the item categories. Data on clinical variables and follow-up questionnaires to assess the construct and criterion validity will be presented at the congress. Conclusions: The SPARRA questionnaire seems to be a reliable scale for evaluating symptoms in persons at risk for RA. More follow-up and data from collaborating centers within Europe is necessary for assessment of the construct, criterion and external validity. References: Stack, Rheumatology 2014; van Tuyl, Musculoskel Care 2015 Disclosure of Interest: None declared